Accounting and the fight against corruption in Italian government procurement: A longitudinal critical analysis (1992–2014). (May 2015) - Sargiacomo, Massimo; Ianni, Luca; D'Andreamatteo, Antonio; Servalli, Stefania
Abstract: In 1992, a political earthquake shook Italy when the corruption and fraud case, "Clean Hands" ("Mani Pulite") exploded into the public eye, and a vast network of corrupt politicians, businessmen and bureaucrats was unveiled. The Italian bureaucratic apparatus was especially implicated in this expose, and it became evident that government procurement practices were shaped by an organizational culture of corruption. This paper develops a critical longitudinal analysis of the subsequent 22-year period to critically assess whether the subsequent introduction of accounting-based anti-corruption assemblages helped to curb corrupt behaviors.